Analisis Pengaruh Variasi Bentuk Shear All terhadap Perilaku Struktur Gedung Bertingkat - Pramesta Armanisag Pangestuti; Agustinus Sungsang Nana Patria; Adam Miskah (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
The development of multistory buildings in earthquake-prone regions requires structural systems capable of limiting lateral displacement and maintaining stability. Shear walls are commonly used to improve lateral stiffness, but their effectiveness depends on cross-sectional shape. This study evaluates the effect of shear wall shape variations on an eight-story reinforced concrete office building and identifies the most effective configuration based on natural period, interstory drift, base shear, internal forces, and structural safety. The building measures 18 × 30 m, has a height of 32 m, and was modeled three-dimensionally using ETABS. Five models were compared: a structure without shear walls and structures with C-shaped, IWF-shaped, I-shaped, and L-shaped shear walls. All models used identical geometry, materials, loading, and seismic parameters in accordance with SNI 1726:2019 and SNI 2847:2019. The results show that Model 1 has the longest period, Model 2 produces the largest drift in the X direction, and Model 3 provides the smallest drift but experiences overstress in the coupling beam. Model 5 causes high internal-force concentration in the beams. Model 4, with an I-shaped shear wall, demonstrates the most balanced performance because it satisfies the allowable drift limit, provides uniform stiffness, controls internal forces, and shows no overstressed elements.